2016
DOI: 10.1152/ajpheart.00632.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fractal regional myocardial blood flows pattern according to metabolism, not vascular anatomy

Abstract: Yipintsoi T, Kroll K, Bassingthwaighte JB. Fractal regional myocardial blood flows pattern according to metabolism, not vascular anatomy. Am J Physiol Heart Circ Physiol 310: H351-H364, 2016. First published November 20, 2015 doi:10.1152/ajpheart.00632.2015.-Regional myocardial blood flows are markedly heterogeneous. Fractal analysis shows strong near-neighbor correlation. In experiments to distinguish control by vascular anatomy vs. local vasomotion, coronary flows were increased in open-chest dogs by stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…These figures are comparable to the experimental value of 0.4 using a similar sample mass (0.2 mg) (Matsumoto and Kajiya, 2001), and close to some experimental estimates using higher sample masses (Mori et al, 1995; Yipintsoi et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These figures are comparable to the experimental value of 0.4 using a similar sample mass (0.2 mg) (Matsumoto and Kajiya, 2001), and close to some experimental estimates using higher sample masses (Mori et al, 1995; Yipintsoi et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…This validation has three related but different aspects (Bassingthwaighte and Beyer, 1991; Yipintsoi et al, 2016). The flow dispersion level (CV), the flow fractal nature (self-similarity), and the flow spatial auto-correlation.…”
Section: Methodsmentioning
confidence: 99%
“…From genome to proteome to morphology to function, developmentally and over time, the heart exhibits features in both the spatial and temporal domains that are amenable to fractal analysis. Features for which FDs have been found in the heart include temporal recordings of signals, such as electrocardiograms14, pulse21, pressure and flow22, 23, as well as arrangements of spatial components such as DNA sequences24, proteins25, extracellular matrix constituents26, trabeculae27, and, as already alluded to, coronaries and infarction scar boundaries28, 29, 30. Spatial fractal patterns in the heart are extracted by imaging instruments and bioinformatics tools at various levels of its organization (genome, proteome, organellar, cellular, tissue, whole-organ), and they can describe the complexity of signalling pathways, metabolic networks, and macroscopic structures28.…”
Section: Biological Systems and Organogenesismentioning
confidence: 99%
“…Clinical, high-resolution myocardial tissue perfusion imaging technologies across modalities, including cardiovascular magnetic resonance (CMR)22, stand to gain from fractal insights into the roles of myocardial local mechanics, metabolism, and regional flows in causing regional myocardial blood flow heterogeneity. Animal-based fractal analysis research of the myocardium using microspheres has shown that, in the absence of coronary disease, regional myocardial blood flow heterogeneity was caused by local, metabolically-driven differences in vasomotor regulation and not by local differences in vascular anatomy23. This revelation — that physiologically there are normally some low-flow regions in the heart that are not at all ischaemic — might be highly clinically relevant.…”
Section: Fractal Applications In Cardiologymentioning
confidence: 99%
“…Fractal dimension analysis can be very useful in medicine; examples of FDA usage in medicine are mammographic image analysis, or estimation of tumor neoangiogenesis or of the pattern of coronary vessels. [10][11][12] Fractal dimension analysis of jaw bone cone beam computed tomography (CBCT) images is useful in the diagnosis of osteoporosis. 13 In our study, we tried to distinguish oral leukoplakia and LP using FDA with a classical white-light examination and PDD.…”
Section: Introductionmentioning
confidence: 99%